Cyclophosphamide pulse therapy as treatment for severe interstitial lung diseases - Schulze, Arik Bernard; Evers, Georg; Kümmel, Andreas; Rosenow, Felix; Sackarnd, Jan; Hering, Jan Philipp; Schülke, Christoph; Engelbertz, Jonas Andreas; Görlich, Dennis; Barth, Peter J; Lenz, Georg; Becker, Heidemarie; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Introduction: Besides invasive or non-invasive ventilation, treatment of severe forms of interstitial lung diseases (ILD) includes immunosuppressive medication. In case of refractory organ- or life-threatening courses of disease, cyclophosphamide pulse therapy can serve as a rescue treatment option. Objectives: To investigate therapeutic and prognostic effects of cyclophosphamide for the treatment of severe forms of ILD on intensive care unit (ICU) we performed this analysis. Methods: Between 2009 and 2017 we identified 14 patients, who were treated on intensive care unit (ICU) with severe forms of ILD. Retrospectively, clinical, radiologic and prognostic data were collected and evaluated. Results: Our analysis demonstrated a prognostic impact of cyclophosphamide on the ILD in general. Whereas pulmonary manifestations of both systemic sclerosis (SSc) and ANCA-associated vasculitis had an improved outcome, a reduced overall survival was found for Goodpasture syndrome (GPS), dermatomyositis (DM), cryptogenic organizing pneumonia (COP) and drug reaction with eosinophilia and systemic symptoms (DRESS; p=0.040, logrank test). Besides, additional plasmapheresis and initiation of cyclophosphamide within ten days following initial diagnosis of ILD were associated with improved prognosis. Conclusion: Positive prognostic effects of cyclophosphamide pulse therapy in ICU treated patients suffering from severe respiratory failure due to pulmonary manifestations of both SSc and ANCA-associated-vasculitis were observed. Further prognostic and therapeutic data are needed for cyclophosphamide for this indication in order to prevent patients from its toxic side-effects, who most likely will not benefit from its application.